Involvement of Family Members and Professionals in Older Women's Post-Fall Decision Making. Issue 3 (4th March 2018) - Bergeron, Caroline D.; Hilfinger Messias, DeAnne K.; Friedman, Daniela B.; Spencer, S. Melinda; Miller, Susan C.
ABSTRACT: This exploratory, descriptive study examined involvement of family members and professionals in older women's post-fall decision making. We conducted semistructured interviews with 17 older women who had recently fallen and 11 individuals these women identified as being engaged in their post-fall decision-making processes. Qualitative data analysis involved open and axial coding and development of themes. After experiencing a fall, these older women's openness to others' opinions and advice; their assessments of types and credibility of potential information sources; and the communication practices they established with these sources influenced how they accessed, accepted, or rejected information from family members and professionals. Increased awareness of the involvement of others in post-fall decision making could enhance communication with older women who fall. Developing and implementing practical strategies to help family members and professionals initiate and engage in conversations about falls and their consequences could lead to more open decision making and improved post-fall quality of life among older women.